Anoftalmia congênita clínica - alterações oculares e sistêmicas associadas - De Souza Segundo, Paulo [UNESP]; Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2006)
Purpose: To describe alterations observed in patients with congenital clinical anophthalmia and the occurrence of association with other ocular and extra ocular abnormalities. Methods: An observational retrospective study was conducted evaluating 12 patients with congenital clinical anophthalmia at Faculdade de Medicina de Botucatu-UNESP, between 1992 and 2005. In those patients it was observed the ocular abnormalities, severity, laterality, follow-up and to systemic abnormalities associated. The congenital clinical anophthalmia have been associated to major severity abnormalities extra-oculars, mainly when the anophthalmia was bilateral, such agenesis of corpus callosum, others craniofacial anomalies and cardiac defects. In the cases unilateral, the alteration associated more frequently was the facial asymmetry, showing the direct correlation between anophthalmos and development of orbit and face. Conclusion: There was relation between congenital clinical anophthalmia and ocular abnormally and extra-ocular abnormally. Patients with bilateral anophthalmos disease have more severe alterations. anophthalmia congenital attends a course with abnormalities of development of the face.
Congenital anophthalmos: Ocular and systemic alterations related
Keywords: Abnormalities; Anophthalmos/epidemiology; Microphthalmos; Retrospective studies